Dietary L-glutamine supplementation improves growth performance, gut morphology, and serum biochemical indices of broiler chickens during necrotic enteritis challenge. (15th March 2018) - Xue, G D; Barekatain, R; Wu, S B; Choct, M; Swick, R A
Abstract: Necrotic enteritis (NE) causes significant economic losses in the broiler chicken industry, especially in birds raised without in-feed antibiotics. L-glutamine (Gln) is an amino acid that may compensate for metabolic losses from infection and improve the intestinal development. This study investigated the effects of dietary Gln (10 g/kg) supplementation on growth performance, intestinal lesions, jejunum morphology, and serum biochemical indices of broiler chickens during NE challenge. The study employed a factorial arrangement of treatments with factors: NE challenge, no or yes; dietary Gln inclusion, 0 g/kg in starter (S), d 0 to 10, grower (G) d 10 to 24, and finisher (F) d 24 to 35; 10 g/kg in S, G, F, or 10 g/kg in S, G only. Each treatment was replicated in 6 floor pens with 17 birds per pen as the experimental unit for performance and 2 birds for other measurements. Challenge significantly reduced bird performance, increased incidence of intestinal lesions, and affected intestinal development and serum biochemical indices. Regardless of challenge, Gln supplementation increased gain ( P < 0.05), feed intake ( P < 0.05), and decreased FCR ( P < 0.05) on d 24. On d 35, Gln improved gain ( P < 0.05) and FCR ( P < 0.001) whereas withdrawing Gln from finisher tended to diminish the beneficial effect on weight gain but not FCR. Dietary Gln reduced lesion scores in the jejunum ( P < 0.01) and ileum ( P < 0.01) in challenged birds. On d 16, Gln increased villus height to crypt depth ratio in unchallenged birds ( P < 0.05) and reduced crypt depth of challenged birds on d 24 ( P < 0.05). Regardless of challenge, supplementation with Gln reduced crypt depth on d 16 ( P < 0.05), and increased villus height ( P < 0.01) and the villus height to crypt depth ratio ( P < 0.001) on d 24. Dietary Gln lowered serum uric acid level regardless of challenge ( P < 0.05). The current study indicates that dietary Gln alleviates adverse effects of NE and may be useful in antibiotic-free diets.